Donor-acceptor-based two-dimensional polymer as a supercapacitor electrode with long cycling stability - Bhagyasree, T. M.; Puthiyaveetil, Priyanka Pandinhare; Kumar, Viksit; Asokan, Kiran; Sreekumar, K.; Babu, Sukumaran Santhosh (New Journal of Chemistry, 2023)
The high demand for energy and energy-storage devices urged organic 2D polymers as a potential candidate in this area. One of the major attractions of 2D polymers in electrochemical applications is their long cycling stability due to their rigid and porous structure. Herein, we developed a 2D polymer comprised of donor-acceptor units exhibiting reasonably good performance as a supercapacitor. The 2D polymer displayed a maximum specific capacitance of 218 F g-1 at a current rate of 0.1 A g-1, a higher power density of 4648.35 W kg-1, and an energy density of 7.05 W h kg-1. In a cycling stability test, it demonstrated a capacitance retention of 70% over 10 000 continuous charge-discharge cycles at a current rate of 2.5 A g-1. Such long cycling stability was attributed to the donor-acceptor units and the crystalline nature of the polymer. The sensible selection of the building blocks of the 2D polymers is crucial for the performance and hence provides scope for improvement. An organic donor-acceptor-based 2D polymer, a promising candidate for energy storage devices, displays a specific capacitance of 218 F g-1, a power density of 4648.35 W kg-1, an energy density of 7.05 W h kg-1, and a capacitance retention of 70% over 10 000 cycles.